North America. - Dower, John, fl. 1838-1846?
This map shows North and Central America and the surrounding areas. Each country is outlined in color and cities, bodies of water, and geographic features are marked and labeled (with relief shown by hachures). At the bottom of the map, there is an elevation chart of North American lakes and mountains as well as a key to the "Classification of Places" (in the lower left corner) which notes various populations.